The simultaneous introduction of the tunicate Styela clava (Herdman, 1881) and the macroalga Undaria pinnatifida (Harvey) Suringar, 1873, in northern Patagonia - Pereyra, Patricio Javier (2015)
Determining which factors contribute to the establishment and spread of an introduced species is a challenge with substantial management implications, especially when that species is found associated with another introduced species. Here, we report for the first time the presence of two introduced species, the macroalga Undaria pinnatifida (Harvey) Suringar, 1873 and the clubbed tunicate Styela clava (Herdman, 1881), in San Antonio Bay (northern Patagonia), where apparent facilitation by the tunicate may be contributing to the establishment of the algae. Because S. clava is an ecosystem engineer and acts as a facilitator for the settlement (and further growth) of other species, it may create habitats that are more suitable for U. pinnatifida invasion at locations not yet colonized by the algae.